Children's Rights in Islam: Towards Gender Equality and Youth Justice - Suud Sarim Karimullah (Universitas Islam Negeri Antasari Banjarmasin, 2023)
This study examines the concept of children's rights in Islam, focusing on two key dimensions, namely gender equality and youth justice. This study uses library research methods by conducting a comprehensive literature analysis to compile and analyze written sources related to children's rights in Islam, gender equality, and justice of the younger generation. Through this approach, the study aims to gain a deeper understanding of the issues. The study results show that Islam has great potential in shaping a more just, inclusive, and sustainable society by applying the principles of children's rights, gender equality, and youth justice. It offers an optimistic view that religious values can be a significant cornerstone in building a better society. Islamic teachings emphasize the importance of providing quality education, protection from exploitation, and meeting children's basic needs as an integral part of the principles of justice in this religion. This includes the economic, social, and moral rights that must be fulfilled to build a brighter future for future generations.